Monetary Frameworks : Is There a Preferred Option for the European Central Bank? - Ramaswamy, Ramana (Washington, D.C. : International Monetary Fund, 1997)
This paper discusses how the size of the monetary union in Europe can influence the choice of the monetary framework. The main conjecture is that the European Central Bank ought to target inflation if monetary union is confined to a 'core' group of countries. However, the decision on whether to target inflation or monetary aggregates is not an unambiguous one if monetary union is EU-wide; the choice of the framework will depend on the type of shocks that are likely to prevail. The arguments motivating these conjectures essentially concern the trade-offs between the viability and credibility of different monetary frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet